A study on role of vitamin D3 in uterine fibroids - Moshika; Sailatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Fibroids are one of the significant non-cancerous growths prevalent in females. Vitamin D is found to have a significant influence in the development of fibroid by suppressing the formation of an impaired extracellular matrix (ECM) due to the abnormal reaction to tissue damage response by regulating it. The study is done to find out the mean vitamin D3 levels among women with fibroids and without fibroids, respectively. Methods: This study was a hospital based analytical study done in the department of obstetrics and gynaecology, Chettinad Hospital and Research Institute, Chennai, India for a period of 18 months. Two groups of 60 each, one group with fibroids and the other without fibroids were recruited. Venous blood was drawn from both groups using venipuncture technique and the serum vitamin D3 levels were estimated and compared. Results: The mean vitamin D3 level was 12.98±7.79 ng/ml for those with fibroids and 44.50±9.60 ng/ml for normal group. The mean value was significantly lesser among those with fibroids than those normal with p value of less than 0.05. The mean vitamin D3 levels were similar between various sizes of fibroids. Conclusions: In this study, the level of vitamin D3 was significantly lower among those with fibroids than those women who did not had any fibroids which shows that normal vitamin D3 levels might be protective against uterine fibroids and vitamin D deficiency can lead to the development of fibroids.